2021
DOI: 10.3389/fbioe.2020.592939
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Organic Compounds From Paper Industry Wastes: Integrated Biotechnological Interventions

Abstract: Synthetic organic compounds (SOCs) are reported as xenobiotics compounds contaminating the environment from various sources including waste from the pulp and paper industries: Since the demand and production of paper is growing increasingly, the release of paper and pulp industrial waste consisting of SOCs is also increasing the SOCs’ pollution in natural reservoirs to create environmental pollution. In pulp and paper industries, the SOCs viz. phenol compounds, furans, dioxins, benzene compounds etc. are produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 124 publications
(116 reference statements)
0
6
0
Order By: Relevance
“…These molecules need more attention because of their prevalence in the atmosphere and can impact negatively the ecosystems and human health (Tripathi et al, 2021 a). These are some of the most carcinogenic, mutagenic, and hazardous pollutants (Jaiswal et al, 2021). The Environmental Protection Agency and the European Union have designated several persistent organic pollutants as priority pollutants and their detection in the extracts confirmed that the secondary treatment was not sufficient in rendering the wastewater safe to be discharged or reuse.…”
Section: Tablementioning
confidence: 99%
“…These molecules need more attention because of their prevalence in the atmosphere and can impact negatively the ecosystems and human health (Tripathi et al, 2021 a). These are some of the most carcinogenic, mutagenic, and hazardous pollutants (Jaiswal et al, 2021). The Environmental Protection Agency and the European Union have designated several persistent organic pollutants as priority pollutants and their detection in the extracts confirmed that the secondary treatment was not sufficient in rendering the wastewater safe to be discharged or reuse.…”
Section: Tablementioning
confidence: 99%
“…Hydroquinone (HQ) plays an active part in several processes, such as a redox mediator in photovoltaic cells [ 19 ], a reducing agent in black and white photographic developers and in the paper industry [ 20 , 21 ]. HQ is contained in cigarette smoke and is formed during the production of coal tar products [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phenols, furans, dioxins, benzenes, and fluorinated compounds are among some of the chemicals produced during bleaching that enter waterways and leach through soil. 22 Perfluorooctanoic sulfonic acid (PFOS) and perfluorooctanoic acid (PFOA) are among the most abundant PFAS that have been detected in paper mill sludge, with lower levels of perfluoroalkyl carboxylic acid (PFCA), perfluorooctane sulfonamide (FOSA), perfluorooctanesulfonamidoacetic acid (FOSAA), 8:2 fluorotelomer sulfonic acid (FTS), 10:2 FTS, 12:2 FTS, 14:2 FTS, N -ethyl perfluorooctane sulfonamido acetic acid ( N -EtFOSAA), and N -ethyl perfluorooctane sulfonamido ethanol ( N -EtFOSE) as shown in Table 1. Table 1 also shows the environmental compartments in which these PFAS were detected.…”
Section: Pfas In the Paper Industrymentioning
confidence: 99%